Description of Knowledge, Vaccination Status and Covid-19 Incidence in Students of the FKK UMJ Nutrition Study Program - Kharisma, Dayu Swasti; Rayhana, Rayhana; Savitri, Yolanda; Utami, Shafira Kurniawaty (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Covid-19 (Corona virus disease 2019) is an acute respiratory infection caused by SARS-COV-2 (Severe Acute Respiratory Syndrome Coronavirus 2). The spread of Covid-19 is quite fast and occurs in various countries throughout the world. The development of the Covid-19 pandemic in Indonesia continues to show progress in a better direction. This is the hard work of all elements of society and the government in implementing health protocols and following the complete dose and booster vaccination program. The aim of this research is to determine the description of knowledge, vaccination status and the incidence of Covid-19 among Nutrition Study Program Students, Faculty of Medicine and Health, Muhammadiyah University, Jakarta. This research is a descriptive study with a cross sectional design. Data was taken using a questionnaire collected online. Of the 81 respondents who met the inclusion criteria, 4 people (5%) were male and 77 people (95%) were female. Respondents' ages varied from 17 (2 people; 2.5%), 18 (10 people; 12.4%), 19 (26 people, 32%), 20 (10 people; 12.4%), 21 (14 people ; 17.3%), 22 (12 people; 14.81%), 23 (6 people; 7.4%), and 27 years (1 person; 1.23%). Each respondent who received 0 doses, 1 dose, 2 doses, 3 doses and 4 doses of vaccination was 1 (1.2%), 1 (1.2%), 32 (39.6%) , 39 (48.14%), and 8 (9.9%) people. The history of exposure to Covid-19 for each respondent was never exposed, exposed once, and exposed twice, totaling 58 (71.6%), 19 (23.5%), and 4 (4.9%) people. 3 (3.7%) respondents had been hospitalized due to exposure to Covid-19, while 78 (96.3) people had never been hospitalized. The level of knowledge of respondents regarding Covid-19 and vaccination was 68 (84%) people with a good level of knowledge, 11 (13.6%) people with a fair level, and 2 (2.4%) people with a poor level of knowledge.